Perancangan Voice User Interface(VUI) Aplikasi Presensi Karyawan Dengan Speech Recognition - Desi Arisandy; Rudi Rudi (Fakultas Informatika, 2020)
As we all know, the very easy and fast spread of COVID-19 can threaten human life. This virus is easily spread from inanimate objects that are touched by sufferers. The use of fingerprint attendance machines in the workplace can be a source of the spread of COVID-19, this needs to be considered for other alternatives to record employee attendance, for example with speech recognition technology or known as automated Speech Recognition (ASR). This technology is needed as an important component to build a Voice user interface (VUI). ASR is a technology for translating speech from the user into text. In addition, the use of ASR can improve communication between human-computer interactions, that is, users can interact with computers using voice. This research is aimed at designing prototype employee attendance application with the VUI concept and speech recognition technology. To speed up design and development process, researchers used the RAD (Rapid Application Development) method. From the results of research using the RAD method, it can be concluded that the application can be designed quickly through prototype modeling together with the user.